Effects of salvianolic acid-A on NIH/3T3 fibroblast proliferation, collagen synthesis and gene expression - Liu, Cheng-Hai (World J Gastroenterol, 2000)
AIM: To investigate the mechanisms of salvianolic acid A (SA-A) against liver fibrosis in vitro. METHODS: NIH/3T3 fibroblasts were cultured routinely, and incubated with 10(-4) mol/L-10(-7) mol/L SA-A for 22 h. The cell viability was assayed by [(3)H]proline incorporation, cell proliferation by [(3)H]TdR incorporation, cell collagen synthetic rate was measured with [(3)H]proline impulse and collagenase digestion method. The total RNA was prepared from the control cells and the drug treated cells respectively, and α (1) I pro-collagen mRNA expression was semi-quantitatively analyzed with RT-PCR. RESULTS: 10(-4) mol/L SA-A decreased cell viability and exerted some cytotoxiciy, while 10(-5) mol/L-10(-7) mol/L SA-A did not affect cell viability, but inhibited cell proliferation significantly, and 10(-6) mol/L SA-A had the best effect on cell viability among these concentrations of drugs. 10(-5) mol/L-10(-6) mol/L SA-A inhibited intracellular collagen synthetic rate, but no significant influence on extracellular collagen secretion. Both 10(-5) mol/L and 10(-6) mol/L SA-A could decrease α (1) I pro-collagen mRNA expression remarkably. CONCLUSION: SA-A had potent action against liver fibrosis. It inhibited NIH/3T3 fibroblast proliferation, intracellular collagen synthetic rate and type I pro-collagen gene expression, which may be one of the main mechanisms of the drug.